Compression fatigue properties and damage mechanisms of a bioinspired nacre-like ceramic-polymer composite. (October 2021) - Tan, Guoqi; Yu, Qin; Liu, Zengqian; Wang, Xuegang; Zhang, Mingyang; Liu, Yanyan; Zhang, Zhefeng; Ritchie, Robert O.
Abstract: Fatigue resistance is invariably critical for structural materials, but is rarely considered in the development of new bioinspired materials. Here the fatigue behavior and damage mechanisms of a nacre-like ceramic (yttria-stabilized zirconia) - polymer (polymethyl methacrylate) composite, which resembles human tooth enamel in its stiffness and hardness, were investigated under cyclic compression to simulate potential service conditions. The composite has a brick-and-mortar structure which exhibits a staircase-like fracture behavior; it displays a transition in cracking mode from the fracture of the ceramic bricks to separation along the inter-brick polymer phase with increasing stress amplitude. The nacre-like structure functions to induce crack deflection, increase the roughness of the crack surfaces, and promote the mutual sliding between bricks during fracture; this results in high fatigue resistance, which enhances the potential of this composite for dental applications. Graphical abstract: Image, graphical abstract